An Analysis of Operations Management’s Impact on Enhancing Manufacturing Processes at Janaki Electromech Private Limited in Nagpur - Jayesh Devidas Baswante, Atul Tikhade (South Eastern European Journal of Public Health, 2025)
Efficient operations management significantly influences the optimization of manufacturing processes in modern industries. This study explores the operational strategies and their impact on enhancing manufacturing efficiency at Janaki Electromech Private Limited in Nagpur. By analysing various elements such as process workflows, resource allocation, and quality control measures, the research evaluates how effective operations management can streamline production cycles and minimize operational bottlenecks. Emphasis is placed on understanding the integration of technology and lean manufacturing principles to achieve sustainable growth and improved productivity. Through a comprehensive case study approach, primary data was collected via interviews with key personnel, complemented by secondary data from company records. The findings reveal a strong correlation between systematic operations management practices and improved manufacturing performance, including reduced production costs and enhanced product quality. Recommendations are provided to further optimize existing processes by adopting innovative tools and employee training programs. This research underscores the critical role of operations management in driving competitiveness and operational excellence in manufacturing sectors.